Bio-nanoplatforms based on carbon dots conjugating with F-substituted nano-hydroxyapatite for cellular imaging. Issue 47 (16th November 2015) - Zhao, Yafei; Shi, Liyi; Fang, Jianhui; Feng, Xin
Abstract : Bio-nanoplatforms based on carboxyl-functionalized carbon dots conjugating with amino terminated F-substituted hydroxyapatite were assembled for cellar imaging. Abstract : Carbon dots (CDs) have shown great promise in a wide range of bioapplications due to their tunable optical properties and noncytotoxicity. For the first time, a rational strategy was designed to construct new bio-nanoplatforms based on carboxylic acid terminated CDs (CDs-COOH) conjugating with amino terminated F-substituted nano-hydroxyapatite (NFAp) via EDC/NHS coupling chemistry. The monodisperse NFAp nanorods were functionalized with o -phosphoethanolamine (PEA) to provide them with amino groups and render them hydrophilic with respect to the ligand exchange process. The CDs-COOH@PEA-NFAp conjugates exhibits bright blue fluorescence under UV illumination, excellent photostability and colloidal stability. Due to their low cytotoxicity and good biocompatibility as determined by methyl thiazolyl tetrazolium (MTT) assay, the CDs-COOH@PEA-NFAp conjugates were successfully applied as bio-nanoplatforms to MCF-7 breast cancer cells for cellular imaging in vitro . More importantly, the functional CDs conjugated to NFAp provide an extended and general approach to construct different water-soluble NFAp bio-nanoplatforms for other easily functionalised luminescent materials. Therefore, these green nanoplatforms may be a prospective candidate for applications in bioimaging or targeted biological therapy and drug delivery.